PERTUMBUHAN ORGAN TANAMAN BUAH NAGA(HYLOCERUS UNDATUS) PADA MEDIUM MS DENGAN PENAMBAHAN BAP DAN SUKROSA - Sulistiami, Ari; Waeniati, Waeniati; Suwastika, I Nengah (Natural Science: Journal of Science and Technology, 2012)
Dragon fruit (Hylocyrus undatus) is a commercial-cultivated plant that has a high economic value and believed to be a healthy-food. Propagation of seedling by tissue culture technique is challenging step during cultivation of these plant. This research was aimed to determine the efeect of sucrose and BAP concentration in the dragon fruit (H. undatus). This experiment was arranged in completely randomized  design with 4 treatments and 3 replications. The treatmnts were : MS0 + 0,5 ppm BAP + 35 g/L sucrose (A1), MS0 + 0,5 ppm BAP + 405 g/L sucrose (A2), MS0 + 0,5 ppm BAP + 45 g/L sucrose (A3), and MS0 + 0,5 ppm BAP + 50 g/L sucrose (A4). The results showed that all medium tested were suitable medium in inducing organs, including emerge of buds, thorns and roots. The best medium in inducing organogenesis of the plant were MS0 + 0,5 ppm BAP + 50 g/L sucrose.